Graft Copolymerization of Styrene‐Maleic Anhydride Onto Poly(Vinyl Chloride) and Its Cross‐linking by Toluene Diisocyanate: Characterization, Thermal, and Mechanical Properties. Issue 4 (3rd April 2019) - Izadpanah, Reza; Rezaei, Mostafa; Talebi, Saeid
Abstract : In this work, styrene‐maleic anhydride (St‐MA) copolymer was successfully grafted onto poly(vinyl chloride) (PVC) by means of chemical method in cyclohexanone medium. In this manner, the effects of various parameters such as total monomer content, monomers ratio, and initiator concentration on the grafting percentage (GP) and acid value (AV) were examined. The graft copolymers were characterized by Fourier‐transform infrared and nuclear magnetic resonance spectroscopy methods. Afterward, the cross‐linking reaction was carried out through MA hydrolysis and condensation reaction between maleic acid and produced diamines, by toluene diisocyanate (TDI) at the presence of hot water. The results showed that the GP and AV of PVC‐g‐(St‐MA) copolymers were considerably higher than those of PVC‐g‐MA and PVC‐g‐St with significant molecular weight. A gel content of 56% was attained with 1 phr TDI in PVC‐g‐(St‐MA) copolymer. The glass transition temperatures and mechanical properties of PVC‐g‐(St‐MA) samples were increased compared to pure PVC. Cross‐linked PVC‐g‐(St‐MA) showed improved mechanical properties than other samples, but the glass transition temperature of PVC backbone in this cross‐linked copolymer was disappeared due to its heavily dense structure. J. VINYL ADDIT. TECHNOL., 25:377–384, 2019. © 2019 Society of Plastics Engineers